INTERPERSONAL COMMUNICATION STRATEGY OF PERFUME CONSULTANTS IN BUILDING BUYER TRUST AT LAB ART MEDAN - Amanda Yasminta; Kasron Nasution (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the interpersonal communication strategies used by perfume consultants to build customer trust at Lab Art Medan. The study employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, observation, and documentation. Three purposively selected informants were selected: the store manager, a perfume consultant, and a customer who had previously participated in a consultation at Lab Art Medan. The results indicate that customer trust is built through a dialogic two-way communication pattern, a personal approach to understanding customer needs, communicative perfume education, and the creation of a comfortable and participatory shopping experience. These strategies enable customers to not only obtain product information but also experience a more personal, relevant, and convincing interaction during the purchasing process. These findings confirm that interpersonal communication functions not merely as a promotional tool but also as a relational mechanism that builds trust and differentiates Lab Art Medan from other, more transaction-oriented perfume stores. Scientifically, this study contributes to enriching the study of interpersonal communication in the context of consultation-based retail services, particularly in the perfume industry, which is heavily influenced by subjective consumer preferences.